GEO-FENCING LOCATION TRACKING SYSTEM USING IOT AND LORA LPWAN FOR COVID-19 MANDATORY SELF-QUARANTINE MONITORING - Idris, Ahmad Syahrin; Malik, Hafizi; Toha, Siti Fauziah (PERINTIS eJournal, 2022)
Initially, quarantine for COVID-19 patients was carried out at specific quarantine centers; however, with large increases in COVID-19 individuals taxing the health system, a self-quarantine at home system was introduced. Nevertheless, self-quarantine at home creates other issues such as non-compliance to the self-quarantine directive and this has led to the spreading of COVID-19 in the community. In this paper, we propose CAGE (COVID-19 Adherence via Geo-fencing E-tracking), an electronic geo-fencing location tracking system using the Internet of Things (IoT) and Long Range Low Power Wide Area Network (LoRa LPWAN) to monitor and ensure adherence to the COVID-19 mandatory self-quarantine at home directive. CAGE incorporates an IoT-based geo-fencing tracking with location data obtained through GPS and the data is communicated to the authorities through LoRA. CAGE consists of a security fuse function that alerts the authorities if the patients have removed the device. CAGE runs on battery power for the whole self-quarantine period and is reusable where once the self-quarantine period is fulfilled; it can be returned and reprogrammed for the next users. Three versions of CAGE prototype have been developed to satisfy the requirements and they were built using off-the-shelf hardware which possesses the potential to integrate many more features with proper power characterization. In comparison to the first prototype, the second achieved the same geofencing performance while using 87% smaller in size and 65% less active current. This research focuses on design choices for Malaysia implementation and suggested multiple electronic prototypes to enforce strict adherence to Malaysia self-quarantine towards low power usage which can be monitored consistently by the authorities and will lead to breaking the chain of the relevant pandemic.